Basal Ganglia Germ Cell Tumors With or Without Sellar Involvement: A Long-Term Follow-Up in a Single Medical Center and a Systematic Literature Review - Zhang, Yi; Wang, Li; Ma, Wenbin; Pan, Hui; Wang, Renzhi; Zhu, Huijuan; Yao, Yong (Frontiers in Endocrinology, 2021)
Background: Basal ganglia germ cell tumors (GCTs) represent an extremely rare subset of tumors about which little is known. Some patients suffered from tumor dissemination, such as sellar involvement. This study aimed to evaluate the independent prognostic risk factors of patients with basal ganglia germ cell tumors with or without sellar involvement. Methods: 16 patients were diagnosed with basal ganglia germ cell tumors at Peking Union Medical College Hospital from January 2000 to December 2020. A literature review was performed on the online databases Medline and PubMed, and 76 cases in the 19 retrieved articles were identified at the same time. The data regarding biochemical tests, radiological examinations and outcomes during follow-up were analyzed. Results: Of 92 patients in this study, 7 patients were clinically diagnosed as germinomas, with the rest 85 patients receiving surgery. 52 patients suffered from multifocal lesions or tumor dissemination. The patients with basal ganglia GCTs demonstrated a significant male predilection. The patients with delayed diagnosis more likely had cognitive disturbance (p = 0.028), mental disturbance (p = 0.047) and diabetes insipidus (p = 0.02). Multivariate analysis demonstrated the independent poor prognostic risk factors of patients with basal ganglia GCTs were the delayed diagnosis (OR 2.33; 95%CI 1.02-5.31), focal radiotherapy (OR 4.00; 95%CI 1.69-9.49) and non-pure germinoma (OR 4.64; 95%CI 1.76-12.22). Conclusions: The delayed diagnosis, focal radiotherapy, and non-pure germinoma were associated with a poorer prognosis for patients with basal ganglia GCTs with or without sellar involvement.